Natural causes : an epidemic of wellness, the certainty of dying, and killing ourselves to live longer - Ehrenreich, Barbara (New York : Twelve, 2018)
Offers insight into healthcare practices, identifying the cellular sources of aging and illness and revealing that aggressive treatments provide an illusion of control and survivability at the cost of life quality.
Keywords: Death -- Sociological aspects; Aging; Death -- Sociological aspects; Aging